Tinjauan Kelengkapan Berkas Persyaratan Klaim Pasien Rawat Inap Covid-19 di Rumah Sakit Sumber Waras - Bahlani; Lily Widjaja; Deasy Rosmala Dewi; Laela Indawati (Yayasan Literasi Sains Indonesia, 2022)
Every hospital organizes a health insurance program, the implementation of the national health insurance program is operated by the Health Office, before the hospital collects payments to the Health Office, a complete inpatient claim requirement file is required, if the inpatient claim requirement file is incomplete it will hamper the process. the health office's claim to the hospital, causing a pending claim. The purpose of this study was to get an overview of the completeness of the claim file requirements for Covid-19 inpatients at Sumber Waras Hospital. The research was conducted using a quantitative descriptive method. The sample in this study was taken from the claim requirements file for Covid-19 inpatients at the Sumber Waras Hospital. Sampling using systematic random sampling. Data was collected using a checklist and interview guidelines submitted to Casmiex officers at Sumber Waras Hospital. Based on the results of a study of 87 files for claim requirements for Covid-19 inpatients, 75.90% were obtained. The factors causing the incompleteness of the Covid-19 inpatient claim file requirements are the Covid-19 inpatient claim requirement file provided by the service officer in hardcopy, the service officer does not provide all the files that exist at the patient's discharge date in that month, the occurrence of errors in inputting patient data and medical support officers do not directly enter the results of laboratory tests. Therefore, it is necessary to disseminate information to service personnel so that they can complete the claim requirements for inpatients in a timely manner.